Tango with the Gringo: the Hard Peg and Real Misalignment in Argentina - Alberola, Enrique (World Bank, Washington, D.C., 2013)
Between 1990 and 2001 the Argentine peso appreciated by 80 percent in real terms, and its overvaluation has been singled out as one of the main suspects in the debate on the causes of the Argentina collapse of late 2001. This paper assesses the degree of real misalignment in Argentina over the Convertibility period using a model in which the equilibrium real exchange rate is defined as the value consistent with (i) a balance of payments position where any current account imbalance is financed by a sustainable flow of international capital (external equilibrium), and (ii) traded/nontraded sector productivity differentials (internal equilibrium). Empirical implementation of the model suggests that the initial real appreciation of the peso, between 1990 and 1993, was consistent with the productivity increases that Argentina enjoyed following the stabilization of the economy after the hyperinflation of the late 1980s. But after 1996 a widening gap opened between the observed real exchange rate and that consistent with a sustainable net foreign asset position. Our estimates indicate that in 2001 the peso was overvalued by over 50 percent. The model allows us to assess how much of the overvaluation resulted from Argentina's inadequate choice of anchor currency and how much from a divergence of fundamentals between the U.S. and Argentina, ultimately due to the maintenance of policies inconsistent with the peg. We find that both factors played a role in the overvaluation accumulated between 1977 and 2001 that preceded the collapse of the Convertibility regime.